Prevalence and Molecular Epidemiology of Transmitted Drug Resistance and Genetic Transmission Networks Among Newly Diagnosed People Living With HIV/AIDS in a Minority Area, China - Yuan, Dan; Yu, Bin; Li, Yiping; Wang, Zixin; Liu, Meijing; Ye, Li; Huang, Yuling; Su, Ling; Zhang, Yan; Api, Laze; Chen, Maogang; Zhou, Chang; et al. (Frontiers in Public Health, 2021)
Introduction Transmitted drug resistance (TDR) can compromise antiretroviral therapy (ART) efficacy. We aimed to understand the molecular epidemiology of TDR and its genetic transmission networks among newly diagnosed people living with HIV/AIDS (PLWH). Methods A total of 1,318 newly diagnosed PLWH, identified in all population-based HIV screening in a HIV-affected county of a minority area of China (i.e., Butuo county), were enrolled between January 1st, 2018 and November 31st, 2018. HIV-1 pol genes sequences were used for phylogenetic and genotypic drug resistance analyses. The genetic transmission networks were identified. Results The prevalence of TDR among newly diagnosed PLWH was 8.12% (107/1,318). Patients in the stage of AIDS (adjusted OR: 2.32) and had a history of sharing a needle≥5 times (adjusted OR: 3.89) were more likely to have an increased risk of TDR. The prevalence of TDR for non-nucleoside reverse transcriptase inhibitors (NNRTIs) is higher than other inhibitors, with a relatively high prevalence of three mutations (V179D/E/DE [4.93%], K103N/KN [3.11%], and E138A/G [1.52%]). A total of 577 (43.78%) pol sequences were involved in the genetic transmission network, with 171 clusters ranging in size from 2 to 91 pol sequences; 37.38% (40/107) of individuals carrying TDR were involved in the network, and individuals with same TDR associated mutations were usually cross-liked. Conclusions Our data suggest a relatively high level of TDR and many transmission clusters among the newly diagnosed PLWH. Targeted intervention, early identification, and monitoring of resistance are warranted to reduce the TDR and prevent the HIV-1 transmission in areas with a high rate of HIV-1.